Resist‐accept‐direct (RAD) considerations for climate change adaptation in fisheries: The Wisconsin experience - Feiner, Zachary S.; Shultz, Aaron D.; Sass, Greg G.; Trudeau, Ashley; Mitro, Matthew G.; Dassow, Colin J.; Latzka, Alexander W.; Isermann, Daniel A.; Maitland, Bryan M.; Homola, Jared J.; Embke, Holly S.; Preul, Michael (Fisheries management and ecology, 2022)
Decision‐makers in inland fisheries management must balance ecologically and socially palatable objectives for ecosystem services within financial or physical constraints. Climate change has transformed the potential range of ecosystem services available. The Resist‐Accept‐Direct (RAD) framework offers a foundation for responding to climate‐induced ecosystem modification; however, ecosystem trajectories and current practices must be understood to improve future decisions. Using Wisconsin's diverse inland fisheries as a case study, management strategies for recreational and subsistence fisheries in response to climate change were reviewed within the RAD framework. Current strategies largely focus on resist actions, while future strategies may need to shift toward accept or direct actions. A participatory adaptive management framework and co‐production of policies between state and tribal agencies could prioritise lakes for appropriate management action, with the goal of providing a landscape of diverse fishing opportunities. This knowledge co‐production represents a process of social learning requiring substantial investments of funding and time.